A Taxonomic Study and The Annual Preseence of The Species Siagona Angustipennis Bates 1892 of Ground Beetles: Order: Coleoptera: Family: Carabidae in Maysan Governoratel/ Iraq - Hashim Alibadi; Alaa Jabbar (University of Thi-Qar Journal of Science, 2021)
This study was conducted on the Carabidae family for the period from 1/12/2018 to 11/30/2019 in Maysan Governorate, the research included a diagnostic study of Siagona angustipennis Bates 1892, which it relies upon the classification of species, genera and families of ground beetles on the study of adult insects. The results showed that the aforementioned species was recorded in Iraq in Maysan province (Qalaat Saleh area) in the months of April, May and June, and the highest population density of adult insects in May was 4 insects / traps, while the insect was not recorded for the remaining months of the year. The most significant diagnostic character of adult insects: Head elongated, wide, antennae thick, filiform, scape twice the length of the second piece, the mandibles are uneven, left mandible is larger than right mandible, pronotum is wide at the front and narrow at the back, midline is clearly low, two side grooves on the disk Uninterrupted on pronotum, the average length of the insect is 11-17 mm.